The Effectiveness of Employee Performance at the Sinjai District Office of Bulupoddo District - Akil, Nursyahrul; Akib, Haedar; Nasrullah, Muh (Jurnal Office, 2020)
Employees are one of the elements of the apparatus that institutionally becomes part of government management to carry out the main tasks and functions in government, development, and community service. This study aims to determine the effectiveness of employee performance at the Bulupoddo District Office in Sinjai Regency. The research method used is descriptive qualitative. Sources of data in this study are primary data sources and secondary data sources. The results of the interviews were obtained from primary data sources referred to as informants, while the main informants, namely the Bulupoddo Sub-District Head while supporting/ordinary informants, namely the staff of the general subdivision and staffing and the people of the Bulupoddo sub-district. The results showed that the effectiveness of employee performance at the Bulupoddo District Office in Sinjai Regency if seen as a whole was effective. This can be seen from the quantity of work, quality of work, knowledge of work, cooperation, determination in work, and initiative.